Fractional solitons for the nonlinear Pochhammer-Chree equation with conformable derivative - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa (Amer Scientific Publishers, 2018)
In this paper, we present new soliton solutions for the time fractional nonlinear Pochhammer-Chree equation (NPCE) with conformable derivative. The generalized tanh function (GTF) method is employed to extract such solutions for the underlying equation. Physical features of some of the obtained soliton solutions are illustrated through 3 and 2 dimensional plots. The GTF method is very efficient in establishing solitons for fractional differential equations.
Keywords: Nonlinear Pochhammer-Chree Equation; Generalized Tanh Method; Exact Solutions; Conformable Derivative